Towards reconstruction of epithelialized cartilages from autologous adipose tissue‐derived stem cells. (1st November 2016) - New, Sophie E.P.; Ibrahim, Amel; Guasti, Leonardo; Zucchelli, Eleonora; Birchall, Martin; Bulstrode, Neil W.; Seifalian, Alexander M.; Ferretti, Patrizia
Abstract: Deformities of the upper airways, including those of the nose and throat, are typically corrected by reconstructive surgery. The use of autologous somatic stem cells for repair of defects could improve quality and outcomes of such operations. The present study explored the ability of paediatric adipose‐derived stem cells (pADSCs), a readily available source of autologous stem cells, to generate a cartilage construct with a functional epithelium. Paediatric ADSCs seeded on the biodegradable nanocomposite polymer, polyhedral oligomeric silsesquioxane poly(ϵ‐caprolactone‐urea) urethane (POSS‐PCL), proliferated and differentiated towards mesenchymal lineages. The ADSCs infiltrated three‐dimensional POSS‐PCL nanoscaffold and chondroid matrix was observed throughout chondrogenically induced samples. In ovo chorioallantoic membrane‐grafted ADSC‐nanoscaffold composites were enwrapped by host vessels indicating good compatibility in an in vivo system. Furthermore, pADSCs could be induced to transdifferentiate towards barrier‐forming epithelial‐like cells. By combining differentiation protocols, it was possible to generate epithelial cell lined chondrogenic micromasses from the same pADSC line. This proof‐of‐concept study appears to be the first to demonstrate that individual pADSC lines can differentiate towards two different germ lines and be successfully co‐cultured. This has important implications for bioengineering of paediatric airways and further confirms the plastic nature of ADSCs. Copyright © 2016 John Wiley & Sons, Ltd.